Identification of the intestinal type gastric adenocarcinoma transcriptomic markers using bioinformatic and gene expression analysis - V. V. Volkomorov; E. S. Grigor’eva; G. S. Krasnov; N. V. Litvyakov; N. A. Lisitsyn; M. I. Voevoda; A. V. Belkovets; S. G. Afanas’ev; N. V. Cherdyntseva (Успехи молекулярной онкологии, 2017)
Introduction. Searching for specific and sensitive molecular tumor markers is one of the important tasks of modern oncology. These markers can be used for early tumor diagnosis and prognosis as well as for prediction of therapeutic response, estimation of tumor volume or to assess disease recurrence through monitoring. Gene expression data base mining followed by experimental validation of results obtained is one of the promising approaches for searching of that kind.Objective: to identify several membrane proteins which can be used for serum diagnosis of intestinal type of gastric adenocarcinoma.Materials and methods. We used bioinformatic-driven search using Gene Ontology and The Cancer Genome Atlas (TCGA) data to identify mRNA up-regulated in gastric cancer (GC). Then, the expression levels of the mRNAs in 55 pare clinical specimens were investigated using reverse transcription polymerase chain reaction.Results. Comparative analysis of the mRNA levels in normal and tumor tissues using a new bioinformatics algorithm allowed to identify 3 high-copy transcripts (SULF1, PMEPA1 and SPARC), intracellular content of which markedly increased in GC. Expression analysis of these genes in clinical specimens showed significantly higher mRNA levels of PMEPA1 and SPARC in tumor as compared to normal gastric tissue. Interestingly more than twofold increase in expression level of these genes was observed in 75 % of intestinal-type GC. The same results were found only in 25 and 38 % of diffuse-type GC respectively.Conclusions. As a result of original bioinforamtic analysis using TCGA data base two genes (PMEPA1 and SPARC) were shown to be significantly upregulated in intestinal-type gastric adenocarcinoma. The findings show the importance of further investigation to clarify the clinical value of their expression level in stomach tumors as well as their role in carcinogenesis.